The narrative practices of hostile environments: the story of the nation-as-family and the story of security - Whittle, Matthew (Frontiers in Human Dynamics, 2023)
This article contributes to research into the importance of storytelling in asylum practice by examining the narratives used to promote and justify Hostile Environment policies. The two narrative practices identified are the ‘story of the nation-as-family’, which defines national belonging predominantly by markers of race and ethnicity, and the ‘story of security’, whereby racialized refugees are framed as potential threats to the nation’s socio-economic stability. The former propagates a notion of consanguinity that works to exclude and silence people seeking asylum from non-European nations. The latter sees the rhetoric of a ‘clash of civilisations’ so central to the ‘War on Terror’ taken up in policy debates about climate-induced migration. An analysis of the way in which these stories are staged and critiqued in the writing of Abdulrazak Gurnah and Stephen Collis reveals how they elide the relationship between forced migration and the history of European colonialism. In exploring this elision, this article insists on the significance of literary texts as spaces where monocultural conceptions of belonging can be confronted, and where understanding Europe’s colonial past is established as an integral part of hearing the stories of refugees in the present.